Direct Asymmetric α-Hydroxylation of Cyclic α-Branched Ketones through Enol Catalysis - Shevchenko, Grigory A.; Pupo, Gabriele; List, Benjamin (Synlett, 2019)
Enantiopure α-hydroxy carbonyl compounds are common scaffolds in natural products and pharmaceuticals. Although indirect approaches towards their synthesis are known, direct asymmetric methodologies are scarce. Herein, we report the first direct asymmetric α-hydroxylation of α-branched ketones through enol catalysis, enabling a facile access to valuable α-keto tertiary alcohols. The transformation, characterized by the use of nitrosobenzene as the oxidant and a new chiral phosphoric acid as the catalyst, delivers a good scope and excellent enantioselectivities.
Keywords: enol catalysis; α-hydroxy ketones; Brønsted acid catalysis; hydroxylation; chiral phosphoric acid